Relationship between Helicobacter Pylori and Parapsoriasis (Annals of Medical Research, 2021)
Aim: Parapsoriasis is a rare skin disorder characterized by erythematous, squamous, atrophic patchy lesions. Its etiopathogenesis and trigger factors still remain unclear. Parapsoriasis cases carry an increased risk of transformation into cutaneous T cell lymphoma. In the literature, there is no data about Helicobacter pylori (H. pylori) frequency in parapsoriasis. This study aims to evaluate the relationship between H. pylori infection and parapsoriasis.Materials and Methods: The study included thirty patients with parapsoriasis who had no dispeptic complaint and thirty healthy individuals. The patient group was divided into two groups as patients with small plaque parapsoriasis (SPP) and those with large plaque parapsoriasis (LPP) based on clinical examination. Carbon 14 urea breath test was performed to evaluate presence of H. pylori in both patient and control groups.Results: Parapsoriasis cases had a significantly higher rate (18/30, 60.0%) of H. pylori positivity than controls (9/30, 30.0%) (p=0.020). Whereas patients with SPP and patients with LPP had similar rates of H. pylori positivity (55.6% vs 44.4%, p=0.279). Comparison of H. pylori status according to gender it was found that majority of H. pylori positive individuals were men, indicating a significant difference (p=0.014).Conclusion: Our results revealed that H. pylori infection is increased in patients with parapsoriasis. Therefore, it was thought that H. pylori may be associated with parapsoriasis and this agent may play a role in the etiopathogenesis of the disease.
Keywords: Carbon 14 urea breath test; etiopathogenesis; emHelicobacter pylori/em; Parapsoriasis